Software Architecture Hour with Neal Ford. (O'Reilly Media, Inc., 2023)
Join us for a special conversation with Neal Ford and Mary and Tom Poppendieck, authors of four books including the groundbreaking 2003 title Lean Software Development: An Agile Toolkit. You'll learn what they think the future of software will look like and discover why what's most meaningful to software development isn't the newest technologies but knowing what value is and what's most important to work on. You'll also hear their insights on how to get from where you are now to where you need to be in a safe, reliable, and scalable way. This is a chance for you to hear from Neal, Mary, and Tom about software, architecture, and their own career journeys. They'll spend a few minutes covering the trends that are influencing architecture, then tell you what you need to know to stay ahead of the curve. What you'll learn and how you can apply it Find out what the future of software may look like Discover why it's essential to consider the value of your software See what's coming next with software architecture This recording of a live event is for you because... You want the chance to hear from Neal Ford and Mary and Tom Poppendieck about software engineering and architecture and what the future may hold for the field. You're looking to enhance your skills and innovate in your organization. Recommended follow-up: Read Software Architecture: The Hard Parts (book) Read Lean Software Development: An Agile Toolkit (book) Read Implementing Lean Software Development: From Concept to Cash (book) Read Leading Lean Software Development: Results Are Not the Point (book) Take Software Architecture by Example (live online course with Neal Ford and Mark Richards) Watch Software Architecture Superstream: Software Architecture Trade-Offs (live event on January 18).